2001
DOI: 10.3758/bf03194443
|View full text |Cite
|
Sign up to set email alerts
|

A Simon effect induced by induced motion and location: Evidence for a direct linkage of cognitive and motor maps

Abstract: It has been argued that two distinct maps of visual space are formed: a cognitive map that is susceptible to illusions, and a motor map that represents the physical world veridically. In the present study, subjects responded to a nonspatial attribute of a visual target stimulus by pressing a left or right key, while an illusory horizontal displacement of the target was induced. A Simon-type effect was obtained to the induced target motion or position shift-that is, responses were faster when the illusory targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
(95 reference statements)
0
14
1
Order By: Relevance
“…Accordingly, it seems to be reasonable to characterize the dorsal channel as a sensorimotor pathway and the ventral channel as (a part of) a perception-action system (Glover 2004;Hommel et al 2001b). Consistent with this claim, recent studies were able to demonstrate that action planning is affected by cognitive illusions (Glover 2002;Glover and Dixon 2001;Kerzel et al 2001) and semantic interference (Glover and Dixon 2002), while action execution is not.…”
Section: On-line Parameter Specificationmentioning
confidence: 73%
“…Accordingly, it seems to be reasonable to characterize the dorsal channel as a sensorimotor pathway and the ventral channel as (a part of) a perception-action system (Glover 2004;Hommel et al 2001b). Consistent with this claim, recent studies were able to demonstrate that action planning is affected by cognitive illusions (Glover 2002;Glover and Dixon 2001;Kerzel et al 2001) and semantic interference (Glover and Dixon 2002), while action execution is not.…”
Section: On-line Parameter Specificationmentioning
confidence: 73%
“…Although the effect of contextual frames is well documented in spatial representation (Burgess, 2006;Kerzel, Hommel, & Bekkering, 2001;Mou, McNamara, Valiquette, & Rump, 2004;Wang & Spelke, 2002;Witkin & Asch, 1948), such effect has been typically confined to spatial tasks, with seemingly no relevance to object perception (e.g., Zhou, Liu, Zhang, & Zhang, 2012). For instance, coding of locations can be influenced by contextual frames through a biased egocentric midline, known as the induced Roelofs effect (Bridgeman et al, 1997;Dassonville, Bridgeman, Kaur Bala, Thiem, & Sampanes, 2004;Roelofs, 1935).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the absence of the Simon effect with smooth motion was interpreted as supporting the attention-shifting account of the Simon effect. However, Kerzel, Hommel, and Bekkering (2001) showed that the Simon effect does not depend on the preparation of saccadic eye movements or attention shifts: In their study a reliable Simon effect occurred to the direction of illusory motion of a stationary target induced by smoothly moving a large frame surrounding the target.…”
Section: Dynamic Compatibilitymentioning
confidence: 96%